Development of Agritourism Based on Seaweed Farming - Sumadi, I Gede; Wiranatha, Agung Suryawan (SOCA: Jurnal Sosial Ekonomi Pertanian, 2023)
Nusa Penida Island in Bali has been known as one of popular tourist destinations in Bali. Despite of tourism, Nusa Penida Island was popular because of the seaweed production. However, the seaweed production has declined in this island due to the domination of tourism development. During the Covid-19 pandemic, some people in this island have back to seaweed farming. This research aimed to find out the potential of seaweed farming as an agritourism, and to propose development strategies for agritourism in this island. Suana Village was chosen as the location of this research because many seaweed farming practices are still existed within this village area. Data was collected by using literature review, observation, interviews, and focus group discussion. Data analysis was undertaken by using Internal-External Factor Analysis, IE Matrix, and SWOT Analysis. Research findings suggested that agritourism based on seaweed farming at Suana Village has some positive supports in terms of tourist attractions, amenities, accessibility, and ancillary services available in this village. The IE Matrix analysis suggested that the grand strategies for the seaweed agritourism development are product development and market penetration. It is also required improvement of human resources. This research results show that it is really important to build up competitiveness of development of seaweed agritourism in order to link tourism and aquaculture in Nusa Penida Island.